Updates in management of abdominal sepsis - Mirla Fontes de Araujo Borges; Roosveni de Sousa Lacerda; Igor de Sousa Oliveira; Sávio Benvindo Ferreira (Open Journal of Biological Sciences - Peertechz Publications, 2023)
Sepsis is an organ dysfunction caused by a disproportionate host response to infection. The condition is responsible for 1 in every 3 admissions to an intensive care unit (ICU) and about 6 million deaths worldwide. As a result of the imbalance in the inflammatory response, immune dysfunction, mitochondrial damage and other pathophysiological processes, sepsis progresses extremely. This research aimed to search the literature for updates inherent to the therapeutic approach of patients with diseases secondary to intra-abdominal sepsis. The present work is a narrative review with a bibliographical survey carried out in the PUBMED and Virtual Health Library (VHL) research bases, through the search strategy using the following descriptors, in both virtual libraries: "sepsis OR surviving sepsis" AND "intra abdominal infection" AND "therapeutic". At the end of reading the articles in full, ten papers were selected, from which it was observed that new recommendations regarding volume operative source control, and use of additional therapies therapy.  The open abdomen technique is being further explored, as well as more in-depth studies on new drugs for this condition, such as acetylcholinesterase inhibitors, and the use of glucocorticoids became contraindicated, due to low scientific evidence. Therefore, it is concluded that, as it is a medical emergency with high mortality, it is relevant to develop scientific research aimed at the effectiveness, feasibility and safety of new forms of management.